Ten unique and charismatic new species of Microgastrinae wasps (Hymenoptera, Braconidae) from North America - Jose Fernandez-Triana (ZooKeys, 2018)
Ten new species within four genera of Microgastrinae parasitoid wasps (Hymenoptera: Braconidae) are described from Canada and United States: Diolcogaster ichiroi, Diolcogaster miamensis, Glyptapanteles pseudotsugae, Microgaster archboldensis, Microgaster syntopic, Microplitis altissimus, Microplitis jorgeluisi, Microplitis juanmanueli, Microplitis julioalbertoi, and Microplitis mariamargaritae. The new taxa are significant because they represent the first North American records of a tropical group (species of the basimacula group in Diolcogaster), exemplify interesting ecological cases (niche-based host selection in Glyptapanteles, syntopic species in Microgaster), and showcase unique morphological features and/or altitudinal records (Microplitis). Most of the new species were collected in protected areas or areas with strong research programs (Archbold Biological Station and hammock forests near Miami, Florida; Great Sand Dunes National Park and Preserve, and Mount Evans Wilderness Area, Colorado; Sapelo Island, Georgia; Tonto National Forest, Arizona), and thus are also of value and interest for conservation and research efforts.